Bot Followers dalam Meningkatkan Tarif Endorse melalui Instagram menurut Fikih Muamalah - nor Fathin Fahimah (Fakultas Syariah Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
In this study discussed how bot followers work in increasing the endorse rates through instagram and fiqh al-muamalah review of its utilization. This research is normative legal research using conceptual approach. The technique of collecting legal materials used is the method of documentation, which is collecting written data obtained from various sources. The analysis method of legal materials conducted is examine, classify, and analyze the legal materials, and draw conclusions from the results of the analysis has been done. The result of this research is that there are some endorsers who use bot followers to increase the number of followers they have in a short time, thereby implicating the increasing of endorse price offered by endorser. In terms of fiqh muamalah, the utilization of bot followers in this case is analogous to bai’ al-najasy because it has the same principle and ‘illat with bai’ al-najasy, i.e. there are sellers and perpetrators of fraud or al-naajisy who served as the perpetrators of fake offers to raise prices. In this case the bot followers are categorized as al-naajisy because bot followers can raise the price of endorse offered by an account.